Creating the conditions for meaningful and effective PPIE in community-based public health research: learning from a UK-wide lived experience panel - Mohasin Ahmed; Jennifer McLean; Cam Donaldson; Michael J. Roy; Rachel Baker (Research Involvement and Engagement)
Abstract Background Research has been criticised for its extractive nature, often neglecting to reciprocate benefits to the communities involved. Addressing this, Patient and Public Involvement and Engagement (PPIE) has emerged as a crucial approach, engaging community members as research partners rather than subjects of research. However, it is important that PPIE is carried out in a meaningful way to avoid tokenism and extraction from communities. This paper reflects on the learning from the PPIE approach of the CommonHealth Assets (CHA) project, which partnered with 14 community-led organisations (CLOs) across the UK to evaluate their impact on health and wellbeing in their communities. Main body The CHA Lived Experience Panel (LEP), comprised of around 13 individuals from the project-partnered CLOs, played a pivotal role in informing and influencing the research process to enhance the relevance and impact of the CHA project. Following community engagement resources, we aimed to create a supportive and inclusive environment for meaningful PPIE. Through the evaluation of the CHA LEP, this paper reports on its successes and limitations to offer recommendations on creating the conditions for meaningful and effective PPIE in community-based public health research. From our evaluation, we found that adequately resourcing PPIE is crucial to its success. PPIE activities require a dedicated facilitator with expertise in working with diverse stakeholders to advocate for the sustained integration of PPIE into the research team, and to support contributors in their engagement. Being adaptive and responsive in your approach, utilising continuous evaluation and accountability in the process is also key. For contributors to have a meaningful impact, they must be engaged from the funding application stage and throughout the early stages of the project. Contributors must work closely with members of the research team at all levels, with researchers committing to facilitating authentic involvement of contributors, accessing training to work with diverse communication needs where required. Conclusion Our findings demonstrate that meaningful and effective PPIE requires a strong, sustained commitment to valuing and integrating patient/public perspectives in research. We add to the knowledge base in this area by offering a practical example of implementing PPIE in community-based research settings.